Long-term Tillage and Nitrogen Fertilization Effects on Soil Properties and Crop Yields - Utomo, Muhajir; Banuwa, Irwan Sukri; Buchari, Henrie; Anggraini, Yunita; Berthiria, . (UNIVERSITY OF LAMPUNG, 2013)
The impact of agricultural intensification on soil degradation now is occurring in tropical countries. The objective of this study was to determine the effect of long-term tillage and N fertilization on soil properties and crop yields in corn-soybean rotation. This long-term study which initiated since 1987 was carried out on a Typic Fragiudult soil at Politeknik Negeri Lampung, Sumatra (105o13’45.5